A New Stage in Medical Technology Development: Medical New-quality Advanced Technology - Zhizheng DU (Yixue yu zhexue)
Modern medical technology has reached a new stage, characterized by artificial manufacturing, regeneration, synthetic, and enhancement of human tissues and organs, and even the recreation of living organisms. Empirical medicine, experimental and evidence-based medicine, and new-quality medicine coexist, which may represent the overall framework of current and future medical development. Compared with traditional medicine, medical new-quality advanced technology has its own connotations and characteristics, with different components, and its practical consequences and impacts are complex and multi-dimensional. Artificial life and artificial humans, though closely related, are fundamentally different. While artificial humans may approach human-like qualities in the future in certain aspects, the boundary between natural humans and artificial humans remains indelible. Artificial life can be ethically justifiable under certain conditions, but artificial human life is deemed nonexistent. Medical new-quality advanced technology can only thrive within a limited scope defined by fundamental ethical norms to benefit humanity.